KEBIASAAN KONSUMSI KOPI DAN POLA PEMBELIAN DI KALANGAN ANAK MUDA - Komar, Deden; Jusdijachlan, Jusdijachlan; Yusuf, Yusuf; Mulyana, Agus; Cahya Fadillah, Eka; Sakinah, Ghaida; Anjana, Lena; Avianti, Trisa (Journal of Sustainable Agribusiness, 2025)
This study aims to analyze coffee consumption behavior among young people, focusing on factors influencing purchase decisions such as taste, quality, price, packaging, and consumer satisfaction. The research employed a quantitative approach using an online questionnaire distributed to 36 respondents aged 17–25. The findings reveal that taste is the primary factor shaping preferences, with 80% of respondents favoring innovative flavors such as matcha and vanilla. Texture and thickness are more valued than aroma. While price affects purchasing decisions, availability and ease of access are more decisive. Attractive packaging design draws more attention than brand reputation, while high satisfaction levels are not yet accompanied by strong emotional loyalty. Overall, coffee consumption among the youth reflects a fusion of function, lifestyle, and digital trends.